The Effectiveness of Physical Activities on Fatigue In The Elderly: A Systematic Review - Hendrik Prayitno Luawo; Tintin Sukartini; Joko Suwito (Universitas STRADA Indonesia, 2020)
The method in preparing this Systematic review is based on literature studies from various electronic databases including Scopus, Proquest, CINAHL, MEDLINE, and ScienceDirect by conducting a comprehensive review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyzes) guidelines. The keywords used are